2019
DOI: 10.1080/13102818.2019.1634488
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of PPAR-gamma activity inhibits cyclooxygenase 2 expression in cortical neurons with N-methyl-d-aspartic acid induced excitatory neurotoxicity

Abstract: This study aimed to investigate the effect of upregulated peroxisome proliferator-activated receptor-gamma (PPAR-c) activity on cyclooxygenase 2 (COX-2) expression and N-methyl-Daspartic acid (NMDA)-induced excitatory neurotoxicity in primary cultured cortical neurons. Rat cortical neurons were cultured for 8 days in vitro, and divided into control, NMDA, MK-801 (selective NMDA antagonist), rosiglitazone (ROSI, PPAR-c agonist), GW9662 (PPAR-c antagonist), NS398 (selective COX-2 antagonist) and NS398 þ ROSI gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…PPAR-gamma controls fatty acid synthesis, glucose metabolism, and adipocyte differentiation [ 23 ]. PPAR gamma activation may protect against neurotoxicity [ 24 ], neurodegeneration, drug dependency [ 25 ], and neuroinflammation [ 26 ]. It was also observed that PPAR gamma enhances antioxidant defence, mitochondrial biogenesis, and oxidative phosphorylation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPAR-gamma controls fatty acid synthesis, glucose metabolism, and adipocyte differentiation [ 23 ]. PPAR gamma activation may protect against neurotoxicity [ 24 ], neurodegeneration, drug dependency [ 25 ], and neuroinflammation [ 26 ]. It was also observed that PPAR gamma enhances antioxidant defence, mitochondrial biogenesis, and oxidative phosphorylation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%